Photodegradation and Adsorption of Fast Green FCF in Tio2-Chitin Suspension - Romeli, Fatimah Julia (2005)
The potential of chitin as co-adsorbent in the photocatalytic degradation of Fast Green in titanium dioxide suspension was investigated. The physico-chemical characteristics of chitin were studied using Analysis of Surface Area and Porosity (ASAP), Fourier Transform Infrared Spectroscopy (FTIR) and Scanning Electron Microscopy (SEM). The sorption study was first done and compared with titanium dioxide heterogeneous photocatalysis. The result of kinetics studies indicates that the sorption process was pH dependent and exothermic. The adsorption equilibrium was achieved after 60 minutes and the adsorption capacity increased as the dye concentration was increased. The kinetic data was tested for first and pseudo-second kinetic order models and was found to fit well to the latter, while the adsorption isotherm was found to agree well with the Langmuir equation assuming monolayer type adsorption.The photocatalytic degradation and adsorption of Fast Green from aqueous solution has been investigated in suspensions containing commercial titanium dioxide (Degussa P-25), chitin and mixture of titanium dioxide-chitin. The removals of Fast Green using a mixture of titanium dioxide-chitin were found to follow first order kinetic. The presence of chitin in titanium dioxide suspension enhanced the removal by two times higher. Fast Green removal using mixture of titanium dioxide-chitin under UV irradiation was found to be more efficient rather than illumination using titanium dioxide or chitin alone. The removal of Fast Green using chitin and a mixture of titanium dioxide-chitin were rapid for the first 30 minute and reached equilibrium after 1 hour. A synergy effect was observed with an increase in the apparent rate constant by 1.86 times. This was ascribed to an extended adsorption of Fast Green on chitin followed by a transfer to titanium dioxide where it is photocatalytically degraded. pH has significant effect on the adsorption and photodegradation properties of chitin and titanium dioxide surface. However, the effect of temperature on adsorption and photodegradation process using titanium dioxide-chitin mixture was minimal. This combined photocatalytic-adsorption system appears promising as an efficient accelerated removal process of organic pollutants from water.